A companion to Sardinian history, 500-1500
1 online resource.
Keywords: The first English-language survey of medieval and modern Sardinia, this volume offers access to long-awaited European scholarship on a critical missing link in the Mediterranean. Based on new archaeological fieldwork and current research from a variety of academic perspectives— architecture, colonialism, ecclesiastic history, cartography, demography, law, musicology, politics, trade, and urban planning—the authors provide the foundation to incorporate Sardinia into a broader European history. Among other contributions, archaeology adds critical insight into the relationship between Christian, Muslim, and Jewish inhabitants of Sardinia, through examinations of urban and rural settlement patterns. This volume aims to stimulate further analysis of the critical role Sardinia has played as one of the largest and most strategically located islands in the Mediterranean. Contributors are Laura Biccone, Nathalie Bouloux, Henri Bresc, Marco Cadinu, Roberto Coroneo, Laura Galoppini, Henrike Haug, Michelle Hobart, Rossana Martorelli, Giampaolo Mele, Marco Milanese, Giovanni Murgia, Gian Giacomo Ortu, Daniela Rovina, Olivetta Schena, Cecilia Tasca, Raimondo Turtas, and Corrado Zedda.